Andrey Kofman: A Creative Personality of the Syncretic Type - Ya. G. Shemyakin (Ибероамериканские тетради)
Andrey Kofman, a prominent Russian researcher in the field of humanities, can be described as a creative personality of the syncretic type, as he was both a researcher and an artist, in the broad sense of the word. A.F. Kofman used two fundamental intellectual strategies in his research, successfully applying them separately and in combination. He mastered the right hemisphere strategy, which seeks to study the object of the investigation as a whole, and the left hemisphere strategy, which implies «splitting» the object for analytical purposes. A.F. Kofman’s work can be used to study the particulars of the humanities in general, especially through the lens of M.M. Bakhtin’s concept. The importance of Kofman’s work goes far beyond the study of Latin American literature that he researched and explored in depth. Kofman’s most significant work centers around Latin America as a «frontier» civilization, which is a peculiar amalgam of unity and diversity. Diversity, which stems from inclusive discourse, is dominant, yet unity sui generis prevails, making this type of civilization uniquely systemic from a sociocultural point of view and different from other types. Andrey Kofman’s work confirms the idea that inclusive discourse defined the key features of the Latin American civilization, especially influencing how it took shape and what it identified with.